Becoming a Scholar Cross-cultural reflections on identity and agency in an education doctorate - Savva, Maria; Nygaard, Lynn P. (UCL Press, 2021)
Becoming a Scholar provides a window into the lives of nine non-traditional doctoral students. As mature, part-time, international students enrolled in a professional doctorate programme, they reflect on the transformation process of becoming scholars, and their narratives provide breadth and depth to themes that represent a diverse cross-section of cultures, identities and communities. Recognising that the process of becoming a scholar is as much internal as it is external, the book provides an opportunity to engage with authentic personal stories that remain firmly rooted in academic literature. By bringing the 'human face' behind the doctoral journey to the forefront, the narratives draw much-needed attention to the personal journey that inevitably parallels and intersects with the academic journey. Although the narratives are drawn from a professional Doctor in Education (EdD) programme based in the UK, the struggles are sure to resonate with a much wider range of doctoral students and academics, sparking lively discussion, debate and reflection. A must-read for students preparing to embark on the doctoral journey, and essential reading for doctoral programmes that wish to equip students with important knowledge about the challenges ahead.